Etanercept-Induced Interstitial Lung Disease in a Patient with Plaque Psoriasis - Lopes, Jorge (2019)
Etanercept is one of the biologic drugs approved for the treatment of psoriasis. Despite its wide use and proven efficacy, few cases of pulmonary toxicity have been reported.We present a patient with psoriasis vulgaris medicated with etanercept. Seven months after its start, the patient developed productive cough, with no fever or constitutional symptoms. The thoracic computerized tomography revealed a pattern of bilateral dense micronodules, with predominance in the superior lobes. After suspension of etanercept, there was symptomatic and imaging resolution, without the need for additional pharmacological treatment. We switched the biologic agent for ustekinumab, with goodtolerance and high efficacy.